2018
DOI: 10.5751/es-10085-230242
|View full text |Cite
|
Sign up to set email alerts
|

Flows of change: dynamic water rights and water access in peri-urban Kathmandu

Abstract: ABSTRACT. Urbanization and the changing climate are increasingly influencing people's access to land and water. Changes in use of, and rights and access to, land and water are most acutely experienced in peri-urban areas. We analyze these changes in peri-urban Kathmandu, Nepal. Increasing pressures on land and growing water needs of an expanding population in Kathmandu Valley are creating new patterns of water use, water-related conflicts, and (in)securities. We use two case studies that are characteristic of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
(31 reference statements)
2
23
0
Order By: Relevance
“…Most respondents confirmed that the level of groundwater has been falling continuously in the last ten years. For peri-urban residents, urbanisation is a process that they can see unfolding in terms of expanding city limits, converting rural agriculture land into residential or industrial zones, and increasing demand for water from surrounding villages (Gomes & Hermans, 2018;Shrestha et al, 2018). Respondents mentioned that the flow of water from their village to Hyderabad city has increased manifold in the last two decades, which has put additional pressure on groundwater.…”
Section: Resultsmentioning
confidence: 99%
“…Most respondents confirmed that the level of groundwater has been falling continuously in the last ten years. For peri-urban residents, urbanisation is a process that they can see unfolding in terms of expanding city limits, converting rural agriculture land into residential or industrial zones, and increasing demand for water from surrounding villages (Gomes & Hermans, 2018;Shrestha et al, 2018). Respondents mentioned that the flow of water from their village to Hyderabad city has increased manifold in the last two decades, which has put additional pressure on groundwater.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies discuss the dynamics of competing claims on water in contested peri-urban spaces (Mehta et al 2014;Narain 2014Narain , 2016Narain and Singh 2017;Shrestha, Roth, and Joshi 2018), but very few studies pay attention to caste-determined water exclusions in peri-urban contexts in South Asia. 1 The few studies that discuss caste and water in peri-urban context (Prakash and Singh 2016;van der Woude 2016;Vij and Narain 2016) often report on the traditional nature of caste-determined water exclusions.…”
Section: Introductionmentioning
confidence: 99%
“…29 This also 19 Narain and Prakash 2016;Shrestha, Roth, and Joshi 2018. 20 Shrestha, Roth, and Joshi 2018;Roth et al 2018. 21 MoUD 2016, 3.…”
Section: Resilience and Community Resilience: A Critical Reviewmentioning
confidence: 99%